Unlocking sustainable development: ASEAN ESG and economic growth implication - Dwi Wibawa, Koerniawan; Sugiharto; Septianto, Tri (Analisis Data Innovation, 2024)
Purpose – Study of the Impact of ESG and Economic Growth on the Sustainable Development Goals Index in ASEAN, The Role of Environmental and Social Governance as Moderators States the Objectives of This Study.Design/methodology/approach – Using a panel autoregressive distributed lag (ARDL) model to investigate short- and long-run relationships among the variables. The SDGI, Environmental Score (ES), Social Score (SS), Governance Score (GS), and Economic Growth (EG) data were collected from reputable international sources. A Hausman test confirms the validity of the model.Findings – The findings suggest that environmental, social, and corporate governance promote the SDG accomplishment in ASEAN countries. Economic growth does improve SDG performance but is a double-edged sword, as its impact is more positive when moderated by the quality of environmental governance. Moreover, social governance reinforces the influence of corporate governance on achieving SDGs. These results emphasize the key importance of governance and sustainable development.Originality/value – The study empirically contributes to the governance-SDG nexus in ASEAN, revealing how governance structures can improve sustainable development. The findings also contribute to the literature on the governance of sustainability and offer policy recommendations on enhancing sustainability development goal (SDG) implementation horizons.Research Implications – Governance mechanisms should be embedded in sustainability policies to complement the implementation of the SDGs, according to the study. Good environmental and social governance can enhance the contribution of economic growth to sustainable development